2015
DOI: 10.1016/j.ijproman.2014.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Toward a model for forming psychological safety climate in construction project management

Abstract: The nature of construction projects and their delivery poses immense challenges to the safety of construction practitioners. Historically, attempts to reduce accidents in project settings have gone through three overlapping stages, i.e. the technical age, the human error age, and lately the socio-technical age (Reason, 1993). In the technical age people adopted technical measures to mitigate or prevent hazards and risks in the project environment, while the human error age focused on efforts to avoid malpracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 128 publications
2
60
0
2
Order By: Relevance
“…One of these studies made an effort to conceptualize safety climate at the individual level; and revealed that trust is a significant characteristic of management in the formation of safety climate as a psychological process (Shen, Tuuli, Xia, Koh, & Rowlinson, 2015). Building the framework of trust to the leader is important to determine behavioral and attitudinal markers of organizational safety outcomes.…”
Section: Leadership Style Trust and Safety Outcomesmentioning
confidence: 99%
“…One of these studies made an effort to conceptualize safety climate at the individual level; and revealed that trust is a significant characteristic of management in the formation of safety climate as a psychological process (Shen, Tuuli, Xia, Koh, & Rowlinson, 2015). Building the framework of trust to the leader is important to determine behavioral and attitudinal markers of organizational safety outcomes.…”
Section: Leadership Style Trust and Safety Outcomesmentioning
confidence: 99%
“…The nature of construction projects and their delivery exposes participants to accidents and dangers. A safety climate serves as a frame of reference for employees to make sense of safety measures in the workplace and adapt to their behaviours [43].…”
Section: Management Techniquementioning
confidence: 99%
“…medical and legal costs) associated with injuries and fatalities (Cantor, 2008). A range of academic studies has investigated how to improve workplace safety (Cornelissen et al, 2014;DeJoy, 2005;Farina et al, 2015;Hale et al, 2010;Kines et al, 2013;Mearns et al, 2003;Morillas et al, 2013;Vredenburgh, 2002) and research on safety has covered a wide range of industries, including the energy and chemicals industries (Bragatto et al, 2015;Mearns et al, 2003;Vinodkumar and Bhasi, 2009), various manufacturing industries (Hermann et al, 2010;Lo et al, 2014;Nenonen, 2013), construction (Choudhry et al, 2007a;Cigularov et al, 2010;Shen et al, 2015), aviation (Evans et al, 2007;Liao, 2015;O'Connor et al, 2011), and mining (He and Song, 2012;Paul and Maiti, 2007;Saleh and Cummings, 2011).…”
Section: Introductionmentioning
confidence: 99%